(untitled) (JURNAL GEOGRAFI, 2025)
Wildfires in peatland areas have disrupted not only ecological systems but also educational continuity in Indonesia, particularly for students living in high-risk zones. This study aims to measure the resilience of senior high school students in Muaro Jambi Regency and explore the role of schools in supporting disaster preparedness and psychosocial well-being. Using a mixed-methods approach, the research integrates quantitative data from 343 students across three wildfire risk zones: high, medium, and low, with qualitative insights from semi-structured interviews with principals of three public senior high schools representing each zone. Resilience was assessed using the Disaster Resilience Scale for Individuals (DRSi), covering six dimensions: knowledge and skills, adaptive capacity, psychological endurance, social connectivity, physical health, and financial capability. Descriptive analysis showed slightly higher resilience scores in high-risk zones, but ANOVA results indicated no statistically significant differences across zones. The qualitative analysis used six thematic indicators: curriculum integration, supporting facilities, teacher roles, external collaboration, social support, and post-disaster recovery. Schools in high-risk zones demonstrated more proactive strategies, including disaster-themed projects, stakeholder coordination, and flexible learning during haze events. The study contributes to the field of education by affirming the relevance of whole-school approaches in disaster risk reduction and highlighting the need for localized, inclusive, and psychosocially responsive educational practices in wildfire-prone regions.